Ascending India and its state capacity : extraction, violence and legitimacy - Ganguly, Sumit; Thompson, William R. (Yale University Press, 2017)
An account of the ongoing struggles and instability of India's political and economic institutions. This study delves into the intricate inner workings of this Asian nation to reveal an Indian state struggling to maintain national security, domestic order, and steady fiscal growth despite weaknesses in its economic and political institutions. The authors' account questions India's perceived strengths and domestic and foreign policy initiatives, while focusing on the infrastructural and economic growth problems, opposition to reform, and other important hurdles the nation has faced and will continue to face over the coming decade and beyond.